My Life as a Spy: Investigations in a Secret Police File - Verdery, Katherine (Duke Univ Pr, 2018)
As Katherine Verdery observes, "There's nothing like reading your secret police file to make you wonder who you really are." In 1973 Verdery began her doctoral fieldwork in the Transylvanian region of Romania, ruled at the time by communist dictator Nicolae Ceausescu. She returned several times over the next twenty-five years, during which time the secret police–the Securitate–compiled a massive surveillance file on her. Reading through its 2,781 pages, she learned that she was "actually" a spy, a CIA agent, a Hungarian agitator, and a friend of dissidents: in short, an enemy of Romania. In My Life as a Spy she analyzes her file alongside her original field notes and conversations with Securitate officers. Verdery also talks with some of the informers who were close friends, learning the complex circumstances that led them to report on her, and considers how fieldwork and spying can be easily confused. Part memoir, part detective story, part anthropological analysis, My Life as a Spy offers a personal account of how government surveillance worked during the Cold War and how Verdery experienced living under it.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Political Survival and Yasukuni in Japan's Relations with China - Cheung, Mong (Routledge, 2018)
What role does the political survival of prime ministers play in Japan’s relations with China over the Yasukuni issue? Three Japanese prime ministers, including Nakasone Yasuhiro, Hashimoto Ryutaro and Abe Shinzo, complied with China’s demands and stopped visiting the controversial Shrine in 1986, 1997 and 2007, respectively. By contrast, the Yasukuni controversy intensified between 2001 and 2006 when a popular Prime Minister Koizumi Junichiro was determined to pay regular homage to the Yasukuni Shrine annually. Prime Minister Abe, who previously demonstrated restraint over the issue in his first term between 2006 and 2007, visited the Yasukuni unexpectedly in 2013 but not in 2014 or 2015. To explain this variation, this book presents an alternative interpretation of Japan’s official responses toward China’s pressure over the Yasukuni issue between 1985 and 2015 by applying a political survival approach that highlights the domestic political legitimacy of the Japanese prime minister or the ruling party.This book will be of great interest to students and researchers of Sino-Japanese relations, Japan’s foreign policy and international relations.
Keywords: References - Boel et al. (2021); Archives and Human Rights

The United Nations Set of Principles to Combat Impunity: A Commentary - Haldemann, Frank; Unger, Thomas (Oxford University Press, 2018)
The fight against impunity has become a growing concern of the international community. Updated in 2005, the UN Set of Principles for the Protection and Promotion of Human Rights Through Action to Combat Impunity is the fruit of several years of study, developed under the aegis of the UN Commission on Human Rights and then affirmed by the Human Rights Council. These Principles are today widely accepted as constituting an authoritative reference point for efforts in the fight against impunity for gross human rights abuses and serious violations of international humanitarian law. As a comprehensive attempt to codify universal accountability norms, the UN Set of Principles marks a significant step forward in the debate on the obligation of states to combat impunity in its various forms. Bringing together leading experts in the field, this volume provides comprehensive academic commentary of the 38 principles. The book is a perfect companion to the document, setting out the text of the Principles alongside detailed analysis, as well as a full introduction and a guide to the relevant literature and case law. The commentary advances debates and clarifies complex legal issues, making it an essential resource for legal academics, students, and practitioners working in fields such as human rights, international criminal law, and transitional justice.
Keywords: References - Boel et al. (2021); Archives and Human Rights

Proof - Peterson, Trudy Huskamp (Informatio, 2018)
This essay looks at the historical background of compensation payments, then considers the impact of World War II on reparations programs, the intellectual criteria for compensation developed by international bodies during the second half of the 20th century, and examples of state-level compensation after 1975 to individuals who were harmed by state actions. It concludes by considering the documents required to prove identity and prove the harm that gives rise to the right to compensation.
Keywords: References - Boel et al. (2021); Archives and Human Rights; References - Comma (2020 1-2); Archives and Human Rights